The studies on the values of alkaline phosphatase (alp), ca and inorganic phosphorus and the effects of combination of lineamycin and gentamycin on the treatment in calevs with enzootic pneumonia - Veysi ASLAN; Mehmet NİZAMLIOĞU (Eurasian Journal of Veterinary Sciences)
This investigation was carried out at the Zootechnical Research Institute in Konya from 1984 to 1985 in winter season on 20 Brown- swiss calves with enzootic pneumonia. In the investigation, to most effected calv;es in the infected herd were chosen. The serum ALP, Ca and inorganic phosphorus values and the elinical controls of calves were determined before and after the treatment. The results of ALP, Ca and inorganic -phosphorus levels before the treatment were found to be 77.1 U/L, 14.9 ının%, 8.2 mm% respectivelly. Liricoriıycin (10 mm/kg) and gentamycin (4 mg/kg) combination was injected intramuscularly to each infected calf for four consecutive days. In addition, prednisolon and antistin ampules were injected in dosage of two ampules for two days intramuscularly. ALP, Ca and inorganic phosphorus levels were determined after the treatment again. The results were foun~ to be. 64.1 U/L, 15.04 mg%, 7.8 mg% respectivelly and all of the calves recovered by this.